Adhesives and adhesive sheets

A pressure-sensitive adhesive using plant-derived raw materials and a specific polyester resin composition addresses the challenges of adhesive properties, processability, and transparency in existing adhesives, achieving excellent performance even when narrowed for use in portable electronic devices.

JP7654976B2Active Publication Date: 2025-04-02MITSUBISHI CHEM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020522396
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-08
Filing Date
2020-04-17
Publication Date
2025-04-02
Estimated Expiration
2040-04-17

AI Technical Summary

Technical Problem

Existing polyester-based adhesives and adhesive sheets, especially those using plant-derived materials, face challenges in achieving excellent adhesive properties, processability, dent resistance, and transparency, particularly when made into thin sheets or narrowed for use in portable electronic devices.

Method used

A pressure-sensitive adhesive with a crosslinked adhesive composition containing a polyester resin that uses plant-derived raw materials such as dimer acids, sebacic acids, and dimer diols, with a polyol component consisting of glycols with even carbon numbers, and an ester group concentration of 2 mmol/g or more, to achieve high adhesive strength and environmental sustainability.

Benefits of technology

The adhesive exhibits excellent adhesive properties for various substrates, including metals and plastics, with improved processability, dent resistance, and transparency, even when narrowed, making it suitable for applications in portable electronic devices and other electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654976000001
    Figure 0007654976000001
  • Figure 0007654976000002
    Figure 0007654976000002
  • Figure 0007654976000003
    Figure 0007654976000003
Patent Text Reader

Abstract

Provided is an adhesive that uses plant-derived, environmentally friendly raw materials, obtained by crosslinking an adhesive composition containing a polyester resin (i) having a structural unit derived from a polycarboxylic acid (a) and a structural unit derived from a polyol component (b) as an adhesive having good adhesive properties and excellent dent resistance and transparency, wherein the polyester resin (i) contains 60 wt% or more relative to the polyester resin (i) of a structural unit derived from at least one selected from the group consisting of dimer acids, sebacic acids, and dimer diols and contains a glycol (b1) having an even number of carbon atoms (however, excluding dimer diols) as the polyol component (b), the ester group concentration of the polyester resin (i) is 2 mmol / g or higher, and the adhesive has an adhesive force (α) of 1 N / 25 mm or higher under specific conditions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester-based adhesive and adhesive sheet, and more specifically to an adhesive that uses environmentally friendly plant-derived raw materials, has good adhesive properties for various adherends such as metals and plastics, and has excellent processability, dent resistance, and transparency. [Background technology]

[0002] In recent years, pressure sensitive adhesives have come to be used for bonding parts, etc., in order to reduce the size and weight of products. As such pressure sensitive adhesives, pressure sensitive adhesives using polyester resins and having excellent adhesive strength are also being considered.

[0003] Meanwhile, in recent years, as part of measures to combat the depletion of fossil fuel resources and global warming, the use of plant-derived raw materials, which are renewable resources, has been recommended, and there is a demand for adhesives with a high degree of bioplasticity that use plant-derived raw materials that are environmentally friendly.

[0004] As an example of such a polyester-based adhesive using a plant-derived raw material, Patent Document 1 describes a polyester-based polymer having an alkyl group on the molecular side chain obtained by a condensation reaction between a plant-derived dicarboxylic acid and a plant-derived diol as the main component, and a moisture permeability of 200 g / m 2 A low moisture permeable pressure-sensitive adhesive sheet having the following pressure-sensitive adhesive layer has been proposed.

[0005] Patent Document 2 proposes a pressure-sensitive adhesive sheet using a polyester containing at least lactic acid units, dibasic acid units, and glycol units, the dibasic acid units containing dimer acid, the polyester having a glass transition temperature of -70 to -20°C when measured at a heating rate of 20°C / min using a differential scanning calorimeter, a weight average molecular weight of 20,000 to 300,000, and a hydroxyl value of 1 to 100 mgKOH / g.

[0006] General polyester resins are crystalline resins, but when used as adhesives, it is important to break down the crystallinity. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2007-308626 A [Patent Document 2] JP 2010-37463 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, the technology disclosed in the above Patent Document 1 uses a long-chain alkyl-based raw material, and the resulting polyester resin itself is very soft. Therefore, although the adhesive has a high bioplasticity and is environmentally friendly, the adhesive is soft and has very poor handleability when made into a narrow adhesive sheet, and since the resin itself is too soft, it is difficult to neatly prepare an adhesive sheet before crosslinking, and the dent resistance of such an adhesive is also poor, so further improvement is required in consideration of achieving both environmental friendliness and adhesive performance.

[0009] For example, in the case of adhesive sheets used to fix display protection members (such as cover glass) of portable electronic devices, it is extremely important to reduce the width of the adhesive sheet from the standpoint of increasing the screen size of the information display unit, improving design, and increasing design freedom.

[0010] When the width of the adhesive sheet is narrowed, the handling of the adhesive sheet becomes difficult. In other words, the surface area of ​​the adhesive sheet is reduced by narrowing the width, but the area of ​​the exposed adhesive on the side of the adhesive sheet remains the same even with the separator film attached, making the handling difficult. Furthermore, when narrowing the width of the adhesive sheet, the adhesive sheet is slit, but since the slit width becomes narrow, problems such as the adhesive layer being pulled by the slit blade tend to occur, which affects the performance of the adhesive sheet and causes problems, and further, the adhesive adheres to the blade, which reduces processability and workability.

[0011] In addition, adhesive sheets that are compatible with the narrowing of display protection components for portable electronic devices, etc., are required to have non-sticky sides and, when slit, to minimize deformation of the adhesive layer and adhesion of the adhesive to the blade. Furthermore, adhesives are required to have excellent dent resistance so that no dents are left even when an external force is applied to the adhesive layer, and to have excellent transparency so that abnormalities such as the inclusion of foreign matter can be detected.

[0012] Although the technology disclosed in Patent Document 2 above provides an adhesive that is highly bioplastic and environmentally friendly, the adhesive still does not have sufficient adhesive properties for adherends. In particular, the balance between holding power and adhesive power required for double-sided tapes and the like is not sufficient. Also, the adhesive properties for adherends that are difficult to adhere to, such as plastic substrates, particularly polyolefin substrates, are still not satisfactory, and further improvement is required.

[0013] Furthermore, the polylactic acid-based polyester disclosed in the technology of Patent Document 2 is a promising plant-derived material, but is prone to hydrolysis and requires high resistance to humidity and heat, making it very difficult to use as an adhesive, and its use is discouraged.

[0014] In view of this background, the present invention provides an adhesive and adhesive sheet that have good adhesive properties for various adherends and excellent processability, dent resistance, and transparency, even though the adhesive uses environmentally friendly plant-derived raw materials. [Means for solving the problem]

[0015] However, the present inventors have discovered that in an adhesive in which an adhesive composition containing a polyester resin is crosslinked, when a polyester resin having a high bioplasticity is used, which uses at least one plant-derived raw material such as dimer acids, sebacic acids, and dimer diol, a glycol component having an even number of carbon atoms is used as the polyol component constituting the polyester resin, and by increasing the ester group concentration of the polyester resin and setting a high specified adhesive strength, it is possible to obtain an adhesive that is environmentally friendly, has good adhesive properties for various adherends, and has excellent processability, dent resistance, and transparency even when made narrow.

[0016] That is, the present invention relates to a pressure-sensitive adhesive obtained by crosslinking a pressure-sensitive adhesive composition containing a polyester resin (i) having a structural portion derived from a polyvalent carboxylic acid (a) and a structural portion derived from a polyol component (b), The polyester resin (i) contains 60% by weight or more of a structural portion derived from at least one selected from the group consisting of dimer acids, sebacic acids, and dimer diols, based on the polyester resin (i); The polyol component (b) contains a glycol (b1) having an even number of carbon atoms (excluding dimer diol), The polyester resin (i) has an ester group concentration of 2 mmol / g or more; The first aspect is an adhesive having an adhesive strength (α) of 1 N / 25 mm or more under the following conditions. Adhesive strength (α): When an adhesive sheet is formed on a substrate with an adhesive layer made of an adhesive, it is attached to a SUS-BA plate adherend and left to stand for 30 minutes in an environment of 23°C and 50% RH, after which the 180-degree peel strength (N / 25 mm) at a peel speed of 300 mm / min against the adherend.

[0017] The present invention also provides a pressure-sensitive adhesive obtained by crosslinking a pressure-sensitive adhesive composition containing a polyester-based resin (ii) having a bioplastic content of 60% or more, the polyester resin (ii) has a structural portion derived from a polyvalent carboxylic acid (a) and a structural portion derived from a polyol component (b), and the polyol component (b) contains a glycol (b1) having an even number of carbon atoms (excluding dimer diol); The polyester resin (ii) has an ester group concentration of 2 mmol / g or more; The second aspect is an adhesive having an adhesive strength (α) of 1 N / 25 mm or more under the following conditions. Adhesive strength (α): When an adhesive sheet is formed on a substrate with an adhesive layer made of an adhesive, it is attached to a SUS-BA plate adherend and left to stand for 30 minutes in an environment of 23°C and 50% RH, after which the 180-degree peel strength (N / 25 mm) at a peel speed of 300 mm / min against the adherend.

[0018] Furthermore, a third aspect of the present invention is a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer containing the pressure-sensitive adhesive according to the first or second aspect.

[0019] Usually, most raw materials with a high degree of bioplasticity are long-chain alkyl-based materials, such as sebacic acid derived from castor oil, dimer acid derived from oleic acid, and dimer diols using the dimer acid. For example, sebacic acid is a monomer with very high crystallinity when made into a polyester resin, and polyester resins derived from sebacic acid are used as crystalline polyester resins. On the other hand, dimer acid and dimer diol are monomers used to soften and water-resistant resins, and in order to improve the physical properties, it is advantageous to have an ester group concentration as low as possible, so it is preferable to reduce the ester group concentration as much as possible.

[0020] In addition, generally, when making an adhesive from a polyester resin, it is necessary to lower the glass transition temperature, so that the crystallinity is broken by using a glycol material containing an alkyl dicarboxylic acid and an alkyl group having 5 or more carbon atoms, for example, a branched glycol such as neopentyl glycol (5 carbon atoms), and the resin is softened by using a glycol with a relatively long chain such as 1,6-hexanediol (6 carbon atoms). These glycol materials can break the crystallinity of the polyester resin, lower the glass transition temperature, and improve the adhesive strength. When using a glycol with a small number of carbon atoms, i.e., a glycol with 4 or less carbon atoms, the softness is insufficient and the adhesive properties are likely to be insufficient, so it is not usually considered that a glycol component with 4 or less carbon atoms is used as the main component.

[0021] However, in the present invention, unexpectedly, even though the polyester resin has a high degree of bioplasticity, a glycol having an even number of carbon atoms is used as the polyol component, and the molecular alignment is improved, thereby designing the resin so as not to actually cause crystallization, and while using long-chain monomers derived from plants, the concentration of ester groups is increased, thereby achieving the object of the present invention.

[0022] For example, when a pressure-sensitive adhesive is made using a polyester resin using dimer acid and dimer diol as the main components, the long main chain and side chain alkyl chains result in a very soft resin, which is significantly inferior in "dent resistance when forming a pressure-sensitive adhesive sheet" and "processability when cutting the finished pressure-sensitive adhesive sheet to the required size." In the present invention, for example, dimer acid and appropriate sebacic acid are used to soften the resin, while small glycols such as ethylene glycol and 1,4-butanediol are used as the glycol to maximize the concentration of ester bonds, which are hard components, thereby improving the dent resistance and processability of the pressure-sensitive adhesive made of a polyester resin.

[0023] Furthermore, for example, when a glycol component with an even number of carbon atoms, such as ethylene glycol or 1,4-butanediol, is used, compared to when a glycol component with an odd number of carbon atoms, such as 1,3-propanediol, is used, it is thought that a structure in which some of the polymer chains are aligned is more likely to be formed, increasing the cohesive force within the resin, and as a result, it is presumed that the adhesive strength required for the double-sided tape will be higher. Effect of the Invention

[0024] The adhesive of the present invention is an adhesive obtained by crosslinking an adhesive composition containing a polyester resin (i) having a structural portion derived from a polyvalent carboxylic acid (a) and a structural portion derived from a polyol component (b), the polyester resin (i) containing at least one structural portion derived from a group consisting of dimer acids, sebacic acids, and dimer diols in an amount of 60% by weight or more relative to the polyester resin (i), and containing a glycol (b1) having an even number of carbon atoms (excluding dimer diols) as the polyol component (b), the ester group concentration of the polyester resin (i) being 2 mmol / g or more, and the adhesive strength (α) under the above conditions being 1 N / 25 mm or more. Therefore, the adhesive is highly bioplastic and environmentally friendly, but contains a polyester resin having a high ester group concentration, has good adhesive properties for various adherends, and has excellent processability, dent resistance, and transparency even when narrowed. Therefore, it can be effectively used as a single-sided or double-sided pressure-sensitive adhesive sheet for use in bonding optical members, or as a single-sided or double-sided pressure-sensitive adhesive sheet for fixing members of portable electronic devices or electronic members.

[0025] When the glycol (b1) having an even number of carbon atoms is an aliphatic glycol having a straight chain structure, a pressure-sensitive adhesive having an excellent balance between crystallinity and cohesive strength can be obtained.

[0026] When the polyvalent carboxylic acid (a) contains 70 mol % or less of the straight-chain carboxylic acid (a1), a pressure-sensitive adhesive having a better balance between crystallinity and cohesive strength can be obtained.

[0027] When the polyol component (b) contains 10 to 100 mol % of glycol (b1) having an even number of carbon atoms, a pressure-sensitive adhesive having superior adhesive strength can be obtained.

[0028] When the glycol (b1) having an even number of carbon atoms is a polyol having 4 or less carbon atoms, a pressure-sensitive adhesive having excellent production stability can be obtained.

[0029] When the acid value of the polyester resin (i) is 10 mgKOH / g or less, a pressure-sensitive adhesive having excellent durability can be obtained.

[0030] When the polyester resin (i) has a bioplastic content of 60% or more, the pressure-sensitive adhesive can be made more environmentally friendly.

[0031] The adhesive of the present invention is an adhesive obtained by crosslinking an adhesive composition containing a polyester resin (ii) having a bioplasticity of 60% or more, the polyester resin (ii) having a structural portion derived from a polyvalent carboxylic acid (a) and a structural portion derived from a polyol component (b), the polyol component (b) containing a glycol (b1) having an even number of carbon atoms (excluding dimer diol), the ester group concentration of the polyester resin (ii) being 2 mmol / g or more, and the adhesive strength (α) under the above conditions being 1 N / 25 mm or more. Therefore, the adhesive has a high bioplasticity and is environmentally friendly, but contains a polyester resin having a high ester group concentration, has good adhesive properties for various adherends, and has excellent processability, dent resistance, and transparency even when narrowed. Therefore, it can be effectively used as a single-sided or double-sided pressure-sensitive adhesive sheet for laminating optical members, or as a single-sided or double-sided pressure-sensitive adhesive sheet for fixing members of portable electronic devices or electronic members.

[0032] When the pressure-sensitive adhesive composition further contains a hydrolysis inhibitor (iii), the pressure-sensitive adhesive can have excellent long-term durability.

[0033] When the pressure-sensitive adhesive composition further contains a crosslinking agent (iv), the pressure-sensitive adhesive composition can have even better adhesive strength.

[0034] When the above PSA composition further contains a tackifier resin (vii), the PSA can have even more excellent adhesive properties.

[0035] Furthermore, if the adhesive has a bioplastic content of 60% or more, the adhesive can be made more environmentally friendly. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0036] The configuration of the present invention will be described in detail below, but these are merely examples of preferred embodiments. In the present invention, the term "carboxylic acids" includes not only carboxylic acids but also carboxylic acid derivatives such as hydrogenated carboxylic acids, carboxylic acid salts, carboxylic acid anhydrides, carboxylic acid halides, and carboxylic acid esters.

[0037] The adhesive composition forming the adhesive of the present invention is an adhesive composition containing a polyester-based resin (i) having a structural portion derived from a polyvalent carboxylic acid (a) and a structural portion derived from a polyol component (b), in which the polyester-based resin (i) contains 60% by weight or more of a structural portion derived from at least one selected from the group consisting of dimer acids, sebacic acids and dimer diols, relative to the polyester-based resin (i), contains a glycol (b1) having an even number of carbon atoms (excluding dimer diols) as the polyol component (b), and contains a polyester-based resin having an ester group concentration of 2 mmol / g or more.

[0038] The adhesive composition forming the adhesive of the present invention is an adhesive composition containing a polyester-based resin (ii) having a bioplasticity of 60% or more, the polyester-based resin (ii) having a structural portion derived from a polyvalent carboxylic acid (a) and a structural portion derived from a polyol component (b), the polyol component (b) containing a glycol (b1) having an even number of carbon atoms (excluding dimer diol), and the polyester-based resin (ii) having an ester group concentration of 2 mmol / g or more.

[0039] Hereinafter, each component constituting the pressure-sensitive adhesive composition of the present invention will be described in order.

[0040] <Polyester Resins (i) and (ii)> The polyester resins (i) and (ii) used in the present invention have a structural portion derived from a polyvalent carboxylic acid (a) and a structural portion derived from a polyol component (b), and are obtained, for example, by copolymerizing a copolymerization component containing the polyvalent carboxylic acid (a) and the polyol component (b).

[0041] [Polycarboxylic acids (a)] In the present invention, in order to increase the degree of bioplasticity, it is preferable to use polyvalent carboxylic acids derived from plants. Examples of the plant-derived polyvalent carboxylic acids include sebacic acids derived from castor oil, dimer acids (mainly having 36 or 44 carbon atoms) derived from oleic acid, linoleic acid, linolenic acid, erucic acid, etc., and succinic acids derived from glucose. Note that, as the dimer acids, in addition to those derived from plants, dimer acids derived from beef tallow can also be used.

[0042] Among the polyvalent carboxylic acids (a), it is preferable to use linear carboxylic acids (a1) in terms of easy availability of raw materials and ease of production, more preferably linear carboxylic acids having 4 to 12 carbon atoms, and even more preferably linear carboxylic acids having 6 to 10 carbon atoms, and sebacic acids are particularly preferable in terms of lowering the glass transition temperature and facilitating adjustment of adhesive properties.

[0043] The polyester resins (i) and (ii) used in the present invention contain a structural portion derived from polyvalent carboxylic acids (a), and preferably contain 70 mol% or less of linear carboxylic acids (a1) as the polyvalent carboxylic acids (a), particularly preferably 5 to 70 mol%, and further preferably 10 to 60 mol%. If the content is too high, the crystallinity tends to increase. If the content is too low, the production stability tends to decrease.

[0044] As the polyvalent carboxylic acid (a), it is preferable to use a dimer acid (a2) in that crystallization is easily prevented, and more preferably a hydrogenated product of a dimer acid.

[0045] The dimer acid (a2) is preferably contained in an amount of 40 mol% or more, particularly preferably 50 mol% or more, and further preferably 60 mol% or more, based on the polyvalent carboxylic acid (a). The upper limit is usually 100 mol%. If the content is too low, the crystallinity tends to increase.

[0046] As the polyvalent carboxylic acids (a), it is also preferable to use linear carboxylic acids (a1) and dimer acids (a2) in combination. When these are used in combination, the molar ratio of (a1):(a2) is preferably 1:99 to 90:10, more preferably 5:95 to 60:40, and particularly preferably 10:90 to 50:50.

[0047] Polyvalent carboxylic acids other than those mentioned above may be used as long as the object of the present invention is not impaired. Examples of such polyvalent carboxylic acids other than those mentioned above include aliphatic dicarboxylic acids such as malonic acids, dimethylmalonic acids, glutaric acids, adipic acids, trimethyladipic acids, pimelic acids, 2,2-dimethylglutaric acids, azelaic acids, fumaric acids, maleic acids, itaconic acids, thiodipropionic acids, diglycolic acids, and 1,9-nonanedicarboxylic acids; phthalic acids, terephthalic acids, isophthalic acids, benzylmalonic acids, diphenic acids, 4,4'-oxydibenzoic acids, and further 1,8-naphthalenedicarboxylic acids, 2, Examples of the dicarboxylic acids include aromatic dicarboxylic acids such as naphthalenedicarboxylic acids, such as 3-naphthalenedicarboxylic acids and 2,7-naphthalenedicarboxylic acids; alicyclic dicarboxylic acids such as 1,3-cyclopentanedicarboxylic acids, 1,2-cyclohexanedicarboxylic acids, 1,3-cyclopentanedicarboxylic acids, 1,4-cyclohexanedicarboxylic acids, 2,5-norbornanedicarboxylic acids, and adamantanedicarboxylic acids; and trivalent or higher carboxylic acids such as trimellitic acids, pyromellitic acids, adamantanetricarboxylic acids, and trimesic acids.

[0048] The above polyvalent carboxylic acids (a) may be used alone or in combination of two or more.

[0049] [Polyol component (b)] In the present invention, in order to increase the degree of bioplasticity, it is preferable to use a polyol component derived from a plant. Examples of the plant-derived polyol component include fatty acid ester diols derived from castor oil, dimer acids (mainly having 36 or 44 carbon atoms) derived from oleic acid, linoleic acid, linolenic acid, erucic acid, etc., and dimer diols obtained by converting their hydrogenated products into diols, bioethylene glycol, biopropylene glycol, biobutylene glycol, etc. Among these, bioethylene glycol and biopropane glycol (1,3-propanediol) are preferred in terms of the ease of increasing the ester group concentration, and bioethylene glycol is particularly preferred.

[0050] In the present invention, it is necessary to use, as the polyol component (b), a glycol (b1) having an even number of carbon atoms (excluding dimer diol) in order to increase molecular alignment and impart cohesive strength while destroying crystallinity.

[0051] Examples of the glycol (b1) having an even number of carbon atoms include aliphatic glycols such as aliphatic glycols having a straight chain structure, such as ethylene glycol, diethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol, and aliphatic glycols having a branched structure, such as 1,2-butanediol, 1,3-butanediol, dipropylene glycol, 2,4-dimethyl-2-ethylhexane-1,3-diol, 2-methyl-1,3-propanediol, and 3-methyl-1,5-pentanediol; Alicyclic glycols such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, adamantanediol, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol; Aromatic glycols such as 4,4'-thiodiphenol, bisphenol S, 4,4'-dihydroxybiphenyl, o-, m- and p-dihydroxybenzene, 2,5-naphthalenediol, and p-xylenediol; and their ethylene oxide and propylene oxide adducts; etc. It is also preferred that such glycols (b1) having an even number of carbon atoms are derived from plants.

[0052] Among the glycols (b1) having an even number of carbon atoms, aliphatic glycols are preferred, and in particular, aliphatic glycols having a straight chain structure are preferred from the viewpoint of the balance between crystallinity and cohesive strength.

[0053] In order to increase the ester bond concentration and from the standpoint of production stability, it is preferable to use, as the glycol (b1) having an even number of carbon atoms, a glycol having 4 or less carbon atoms, and it is particularly preferable to use a glycol having 2 carbon atoms.

[0054] Preferred specific examples of the glycol (b1) having an even number of carbon atoms used in the present invention include aliphatic glycols having a straight-chain structure and a carbon number of 4 or less, such as ethylene glycol, diethylene glycol, and 1,4-butanediol. Among these, ethylene glycol and 1,4-butanediol are preferred, and ethylene glycol is particularly preferred.

[0055] In the present invention, the content of the glycol (b1) having an even number of carbon atoms is preferably 10 to 100 mol % based on the total polyol component (b), particularly preferably 30 to 99.9 mol %, further preferably 50 to 99.7 mol %, and particularly preferably 70 to 99.6 mol %. If the content is too low, the adhesive performance tends to decrease.

[0056] In the present invention, a polyol component (b) other than the glycol (b1) having an even number of carbon atoms may be used as long as the object of the present invention is not impaired. Examples of the polyol component (b) other than the glycol (b1) having an even number of carbon atoms include glycols having an odd number of carbon atoms and trihydric or higher polyhydric alcohols.

[0057] Examples of the glycol having an odd number of carbon atoms include aliphatic glycols having a straight chain structure, such as 1,3-propanediol, 1,5-pentanediol, and 1,9-nonanediol, and aliphatic glycols having a branched structure, such as 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, and 2,2,4-trimethyl-1,6-hexanediol; alicyclic glycols such as spiroglycol; Aromatic glycols such as 4,4'-methylenediphenol, bisphenol A, bisphenol fluorene, etc., and their ethylene oxide and propylene oxide adducts; etc.

[0058] Examples of the trihydric or higher polyhydric alcohol include pentaerythritol, dipentaerythritol, tripentaerythritol, glycerin, trimethylolpropane, trimethylolethane, 1,3,6-hexanetriol, and adamantanetriol.

[0059] Among these, glycols having an odd number of carbon atoms are preferred in terms of breaking down crystallinity and improving solution stability, and aliphatic glycols having a branched structure are more preferred, and among these, 2,2-dimethyl-1,3-propanediol (neopentyl glycol) and 2-ethyl-2-isobutyl-1,3-propanediol are preferred in terms of versatility.

[0060] In addition, when the polyvalent carboxylic acids (a) have a high bioplasticity, the polyol component (b) may be a polyol component not derived from plants in terms of ease of polycondensation. However, even in this case, it is preferable to use a polyol having 4 or less carbon atoms, and particularly a polyol having 2 carbon atoms, in order to increase the bioplasticity. That is, when a polyol component (b) having a small carbon number of 4 or less is used, the weight ratio of the carboxylic acids (a) having a high bioplasticity as the polyester resins (i) and (ii) increases, and the bioplasticity can be increased. Specific examples of the polyol having 4 or less carbon atoms include ethylene glycol and 1,4-butanediol.

[0061] The above polyol component (b) may be used alone or in combination of two or more.

[0062] In addition to the above polyol component (b) and polyvalent carboxylic acids (a), compounds having both a carboxylic acid and a hydroxyl group in the molecule (e.g., lactic acid, etc.) can also be used within a range that does not impair the effects of the present invention. However, since lactic acid is easily hydrolyzed, it is more preferable not to use it.

[0063] In order to obtain a high bioplasticity, the polyester resins (i) and (ii) used in the present invention preferably contain at least one selected from the group consisting of dimer acids, sebacic acids, and dimer diols in an amount of 60% by weight or more, more preferably 65% ​​by weight or more, even more preferably 70% by weight or more, and particularly preferably 80% by weight or more, based on the copolymerization components of the polyester resin (i). The upper limit is 100% by weight. If the content is low, the bioplasticity of the resulting polyester resins (i) and (ii) tends to be low, and the reduction in environmental load tends to be insufficient.

[0064] [Production of polyester resins (i) and (ii)] In the present invention, the polyester resins (i) and (ii) can be produced by polycondensation reaction of polyvalent carboxylic acids (a) and polyol component (b) in the presence of a catalyst by a known method, and in the polycondensation reaction, an esterification reaction or an ester exchange reaction is carried out first, and then the polycondensation reaction is carried out. When it is not necessary to make the molecular weight high, the polyester resins (i) and (ii) may be produced by only the esterification reaction or the ester exchange reaction.

[0065] In such an esterification reaction or transesterification reaction, a catalyst is usually used, and specific examples thereof include titanium-based catalysts such as tetraisopropyl titanate and tetrabutyl titanate, antimony-based catalysts such as antimony trioxide, germanium-based catalysts such as germanium dioxide, and catalysts such as zinc acetate, manganese acetate, and dibutyltin oxide, and one or more of these are used. Among these, antimony trioxide, tetrabutyl titanate, germanium dioxide, and zinc acetate are preferred from the viewpoint of the balance between high catalytic activity and the hue of the resulting reaction product.

[0066] The amount of the catalyst is preferably 1 to 10,000 ppm, particularly preferably 10 to 5,000 ppm, and further preferably 20 to 3,000 ppm, based on the total copolymerization components (weight basis). If the amount is too small, the polymerization reaction tends not to proceed sufficiently, whereas if the amount is too large, there is no advantage such as shortening the reaction time, and side reactions tend to occur easily.

[0067] The reaction temperature during the esterification reaction is preferably 200 to 300° C., particularly preferably 210 to 280° C., and further preferably 220 to 260° C. If the reaction temperature is too low, the reaction tends not to proceed sufficiently, and if the reaction temperature is too high, side reactions such as decomposition tend to occur easily. The pressure during the reaction is usually normal pressure.

[0068] As reaction conditions for the polycondensation reaction carried out after the above-mentioned esterification reaction or transesterification reaction, it is preferable to further mix the same amount of the same catalyst as that used in the above-mentioned esterification reaction or transesterification reaction, set the reaction temperature at preferably 220 to 280° C., particularly preferably 230 to 270° C., and gradually reduce the pressure of the reaction system to finally carry out the reaction at 5 hPa or less. If the reaction temperature is too low, the reaction tends not to proceed sufficiently, and if it is too high, side reactions such as decomposition tend to occur easily.

[0069] Thus, the polyester resins (i) and (ii) used in the present invention are obtained.

[0070] In order to make the polyester resin (i) used in the present invention have a high bioplasticity, it is important that the polyester resin (i) contains at least one structural part selected from the group consisting of dimer acids, sebacic acids, and dimer diols in an amount of 60% by weight or more, preferably 65% ​​by weight or more, more preferably 70% by weight or more, and particularly preferably 80% by weight or more, based on the polyester resin (i). The upper limit is 100% by weight. If the content of such structural parts is low, the bioplasticity of the polyester resin (i) will be low, and the reduction of the environmental load will be insufficient.

[0071] The ester group concentration of the polyester resins (i) and (ii) is 2 mmol / g or more, preferably 2.5 to 10 mmol / g, more preferably 2.7 to 7 mmol / g, and particularly preferably 3 to 5 mmol / g. If the ester group concentration is too low, the polyester resin becomes soft and has poor resistance to dents and processability. Examples of methods for adjusting the ester group concentration within a predetermined range include a method of selecting a polyol having 4 or less carbon atoms as the polyol component (b), a method of increasing the content of linear carboxylic acids (a1) as the polyvalent carboxylic acids (a), and a method of combining both of these.

[0072] The ester group concentration (mmol / g) refers to the number of moles of ester bonds in 1 g of polyester resin, and is calculated from the amount of each component charged, for example. The calculation method is to divide the number of moles of the polyvalent carboxylic acid (a) or the polyol component (b), whichever is less, by the total weight of the finished product, and an example of the calculation formula is shown below. Note that when a monomer having both a carboxylic acid and a hydroxyl group is used, or when polyester is produced from caprolactone or the like, the calculation method will be changed as appropriate.

[0073] <When the amount of polyvalent carboxylic acids (a) is small> Ester group concentration (mmol / g) = [(A1 / a1 × m1 + A2 / a2 × m2 + A3 / a3 × m3 ) / Z] × 1000 A: Amount of polyvalent carboxylic acid (a) (g) a: Molecular weight of polyvalent carboxylic acid (a) m: number of carboxy groups per molecule of polyvalent carboxylic acid (a) Z: Finished weight (g)

[0074] <When the amount of polyol component (b) is small> Ester group concentration (mmol / g) = [(B1 / b1 × n1 + B2 / b2 × n2 + B3 / b3 × n3 ) / Z] × 1000 B: Amount of polyol component (b) charged (g) b: Molecular weight of polyol component (b) n: number of hydroxyl groups per molecule of polyol component (b) Z: Finished weight (g)

[0075] The ester group concentration can also be measured by a known method such as NMR.

[0076] In the present invention, the bioplasticity of the polyester resin (i) is preferably 60% or more, more preferably 65% ​​or more, further preferably 70% or more, and particularly preferably 80% or more. If the bioplasticity is low, the reduction of the environmental load tends to be insufficient.

[0077] The bioplasticity of the polyester resin (ii) is 60% or more, preferably 65% ​​or more, more preferably 70% or more, and particularly preferably 80% or more. If the bioplasticity is low, the reduction of the environmental load is insufficient.

[0078] The upper limit of the bioplastic degree is 100%. Methods for adjusting the bioplastic degree to within a predetermined range include using mainly plant-derived polyvalent carboxylic acids or plant-derived polyol components, and it is particularly preferable to use plant-derived polyvalent carboxylic acids (a) in order to efficiently increase the bioplastic degree.

[0079] Here, the bioplastic degree of the polyester resins (i) and (ii) refers to the proportion of carbon from plant-derived raw materials used in producing the polyester resins (i) and (ii) incorporated into the resin relative to the total carbon in the polyester resins (i) and (ii), and is calculated as follows:

[0080] The bioplastic degree of the polyvalent carboxylic acids (a), the polyol component (b) and other components (e.g., compounds having a carboxyl group and a hydroxyl group in the molecule) is calculated from the weighted average of the respective bioplastic degrees.

[0081] (Calculation method) <When polycondensation reaction is involved> Bioplastic content (%) = ((number of moles of carbon in plant-derived monomers when the molar ratio of each component is calculated from the molar ratio of the charged amounts of polyvalent carboxylic acids (a) and polyol component (b) assuming a molar ratio of carboxyl groups to hydroxyl groups of 1:1) / (number of moles of carbon in all constituent monomers)) × 100 <When no polycondensation reaction is involved> Bioplastic content (%) = [(number of moles of carbon in plant-derived monomers) / (number of moles of carbon in all constituent monomers)] x 100

[0082] The bioplastic degree can also be determined by analyzing the composition ratio of a resin by NMR and calculating the carbon number of the plant-derived monomer / the total carbon number.

[0083] Furthermore, the bioplastic content can also be measured by a method conforming to "ASTM D-6866" [measurement of natural radioactive carbon (C-14) concentration].

[0084] The heat of crystalline fusion of the polyester resins (i) and (ii) measured by a differential scanning calorimeter (DSC) is preferably 10 J / g or less, more preferably 5 J / g or less, even more preferably 2 J / g or less, and particularly preferably no heat of crystalline fusion occurs. If the heat of crystalline fusion is too large, crystallinity occurs, and the storage stability of the resin solution tends to be poor, and when made into a pressure-sensitive adhesive sheet, the stability and adhesive properties at low temperatures tend to be poor.

[0085] Examples of methods for adjusting the heat of crystalline fusion within a predetermined range include a method of appropriately using polyvalent carboxylic acids having an alkyl group on the side chain or a polyol component having an alkyl group on the side chain, and a method of using three or more copolymerizable monomer components, preferably four or more copolymerizable monomer components.

[0086] The heat of crystalline fusion means the energy consumed when a crystallized substance is heated and melted, and can be measured by a differential scanning calorimeter (DSC).

[0087] The weight average molecular weight of the polyester resins (i) and (ii) is preferably 2000 to 500000, more preferably 10000 to 300000, and particularly preferably 50000 to 150000. If the weight average molecular weight is too large, the handleability decreases, so a large amount of solvent is required, which tends to increase the environmental load, whereas if the weight average molecular weight is too small, the adhesive properties tend to decrease.

[0088] The weight-average molecular weights shown above are those calculated based on the molecular weight of standard polystyrene. The high-performance liquid chromatograph (HLC-8320GPC, manufactured by Tosoh Corporation) was used with a column: TSKgel SuperMultipore HZ-M (molecular weight exclusion limit: 2×10 6 The measurement is performed using two columns in series (theoretical plate number: 16,000 plates / column, filler material: styrene-divinylbenzene copolymer, filler particle size: 4 μm).

[0089] The acid value of the polyester resins (i) and (ii) is preferably 10 mgKOH / g or less in order to prevent hydrolysis and increase durability, more preferably 5 mgKOH / g or less, particularly preferably 2 mgKOH / g or less, and especially preferably 1 mgKOH / g or less. If the acid value is too large, durability tends to decrease. The acid value can be adjusted, for example, by increasing the ratio of the polyol component (b) during the esterification reaction or transesterification reaction, or by adjusting the reaction conditions. The lower limit of the acid value is usually 0 mgKOH / g.

[0090] The acid values ​​of the polyester resins (i) and (ii) are determined by neutralization titration in accordance with JIS K0070. In the present invention, the acid value means the content of carboxy groups in the polyester resins (i) and (ii). The carboxy groups include those in a carboxylate ion state in which the carboxy groups are neutralized with a basic compound.

[0091] The glass transition temperature (Tg) of the polyester resins (i) and (ii) is preferably −90 to 20° C., particularly preferably −80 to 0° C., further preferably −60 to −20° C., and particularly preferably −50 to −30° C. If the glass transition temperature (Tg) is too high, the adhesive property of the resulting pressure-sensitive adhesive composition tends to decrease, whereas if it is too low, the heat resistance and cohesive strength tend to decrease. The glass transition temperature can be adjusted, for example, by introducing an aromatic skeleton or by changing the alkyl chain length of the polyvalent carboxylic acid component or glycol component.

[0092] The glass transition temperature (Tg) is measured using a differential scanning calorimeter DSC Q20 manufactured by TA Instruments, Inc. The measurement temperature range is −90 to 100° C., and the temperature rise rate is 10° C. / min.

[0093] The pressure-sensitive adhesive composition of the present invention preferably contains, in addition to the polyester resin (i) or (ii), for example, a hydrolysis inhibitor (iii), a crosslinking agent (iv), a urethanization catalyst (v), an antioxidant (vi), a tackifier resin (vii), and the like.

[0094] <Hydrolysis inhibitor (iii)> The hydrolysis inhibitor (iii) is contained in order to ensure long-term durability. As the hydrolysis inhibitor (iii), a conventionally known compound can be used, for example, a compound that reacts with and bonds to the carboxyl terminal of the polyester resins (i) and (ii), specifically, for example, a compound containing a functional group such as a carbodiimide group, an epoxy group, an oxazoline group, etc. Among these, a carbodiimide group-containing compound is preferred because it has a high effect of eliminating the catalytic activity of the proton derived from the carboxyl terminal.

[0095] As the carbodiimide group-containing compound, a known carbodiimide having one or more carbodiimide groups (-N=C=N-) in the molecule can usually be used, but in order to improve durability under high temperature and high humidity, a compound having two or more carbodiimide groups in the molecule, i.e., a polyvalent carbodiimide compound, is preferred, and in particular, a compound having three or more, further five or more, and especially seven or more carbodiimide groups in the molecule is preferred. The number of carbodiimide groups in the molecule is usually 50 or less, and if there are too many carbodiimide groups, the molecular structure becomes too large, so compatibility tends to decrease. It is also preferred to use a high molecular weight polycarbodiimide produced by decarboxylation condensation reaction of diisocyanate in the presence of a carbodiimide catalyst.

[0096] Furthermore, in terms of storage stability, it is preferable that the terminal isocyanate group of the high molecular weight polycarbodiimide is blocked with a blocking agent. Examples of the blocking agent include compounds having active hydrogen that reacts with the isocyanate group, or compounds having an isocyanate group. For example, monoalcohols, monocarboxylic acids, monoamines, and monoisocyanates each having one substituent selected from a carboxy group, an amino group, and an isocyanate group are included.

[0097] Examples of such high molecular weight polycarbodiimides include those obtained by subjecting the following diisocyanates to a decarboxylation condensation reaction.

[0098] Examples of such diisocyanates include 4,4'-diphenylmethane diisocyanate, 3,3'-dimethoxy-4,4'-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, 4,4'-diphenylether diisocyanate, 3,3'-dimethyl-4,4'-diphenylether diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 1-methoxyphenyl-2,4-diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and tetramethylxylylene diisocyanate, which may be used alone or in combination of two or more. Such high molecular weight polycarbodiimides may be synthesized or commercially available products may be used.

[0099] Examples of commercially available products of the carbodiimide group-containing compound include the Carbodilite (registered trademark) series manufactured by Nisshinbo Chemical Inc. Among these, Carbodilite (registered trademark) "V-01", "V-02B", "V-03", "V-04K", "V-04PF", "V-05", "V-07", "V-09", and "V-09GB" are preferred because of their excellent compatibility with organic solvents.

[0100] As the epoxy group-containing compound, for example, a glycidyl ester compound or a glycidyl ether compound is preferable.

[0101] Specific examples of the glycidyl ester compound include benzoic acid glycidyl ester, t-Bu-benzoic acid glycidyl ester, p-toluic acid glycidyl ester, cyclohexane carboxylic acid glycidyl ester, pelargonic acid glycidyl ester, stearic acid glycidyl ester, lauric acid glycidyl ester, palmitic acid glycidyl ester, behenic acid glycidyl ester, versatic acid glycidyl ester, oleic acid glycidyl ester, linoleic acid glycidyl ester, linoleic acid glycidyl ester, behenolic acid glycidyl ester, stearolic acid glycidyl ester, terephthalic acid diglycidyl ester, isophthalic acid Examples of the diglycidyl ester include diglycidyl ester of phthalic acid, diglycidyl ester of naphthalenedicarboxylic acid, diglycidyl ester of methyl terephthalic acid, diglycidyl ester of hexahydrophthalic acid, diglycidyl ester of tetrahydrophthalic acid, diglycidyl ester of cyclohexanedicarboxylic acid, diglycidyl ester of adipic acid, diglycidyl ester of succinic acid, diglycidyl ester of sebacic acid, diglycidyl ester of dodecanedioic acid, diglycidyl ester of octadecanedicarboxylic acid, triglycidyl ester of trimellitic acid, and tetraglycidyl ester of pyromellitic acid. These may be used alone or in combination of two or more.

[0102] Specific examples of the glycidyl ether compound include phenyl glycidyl ether, o-phenyl glycidyl ether, 1,4-bis(β,γ-epoxypropoxy)butane, 1,6-bis(β,γ-epoxypropoxy)hexane, 1,4-bis(β,γ-epoxypropoxy)benzene, 1-(β,γ-epoxypropoxy)-2-ethoxyethane, 1-(β,γ-epoxypropoxy)-2-benzyloxyethane, 2,2-bis-[р-(β,γ-epoxypropoxy)phenyl]propane, and bisphenols such as 2,2-bis-(4-hydroxyphenyl)propane and 2,2-bis-(4-hydroxyphenyl)methane, and bisglycidyl polyethers obtained by reacting epichlorohydrin, and these can be used alone or in combination of two or more kinds.

[0103] The oxazoline group-containing compound is preferably a bisoxazoline compound. Specifically, for example, 2,2'-bis(2-oxazoline), 2,2'-bis(4-methyl-2-oxazoline), 2,2'-bis(4,4-dimethyl-2-oxazoline), 2,2'-bis(4-ethyl-2-oxazoline), 2,2'-bis(4,4'-diethyl-2-oxazoline), 2,2'-bis(4-propyl-2-oxazoline), 2,2'-bis(4-butyl-2-oxazoline), 2,2'-bis(4-hexyl-2-oxazoline), 2 ,2'-bis(4-phenyl-2-oxazoline), 2,2'-bis(4-cyclohexyl-2-oxazoline), 2,2'-bis(4-benzyl-2-oxazoline), 2,2'-p-phenylenebis(2-oxazoline), 2,2'-m-phenylenebis(2-oxazoline), 2,2'-o-phenylenebis(2-oxazoline), 2,2'-p-phenylenebis(4-methyl-2-oxazoline), 2,2'-p-phenylenebis(4,4-dimethyl- 2-oxazoline), 2,2'-m-phenylenebis(4-methyl-2-oxazoline), 2,2'-m-phenylenebis(4,4-dimethyl-2-oxazoline), 2,2'-ethylenebis(2-oxazoline), 2,2'-tetramethylenebis(2-oxazoline), 2,2'-hexamethylenebis(2-oxazoline), 2,2'-octamethylenebis(2-oxazoline), 2,2'-decamethylenebis(2-oxazoline), 2,2'-ethylenebis Examples of such bis(4-methyl-2-oxazoline), 2,2'-tetramethylenebis(4,4-dimethyl-2-oxazoline), 2,2'-9,9'-diphenoxyethanebis(2-oxazoline), 2,2'-cyclohexylenebis(2-oxazoline), 2,2'-diphenylenebis(2-oxazoline), etc., among which 2,2'-bis(2-oxazoline) is most preferred from the viewpoint of reactivity with polyester resins (i) and (ii). These can be used alone or in combination of two or more.

[0104] The hydrolysis inhibitor (iii) preferably has low volatility, and therefore it is preferable to use one having a high number average molecular weight, which is usually 300 to 10,000, and preferably 1,000 to 5,000.

[0105] In addition, from the viewpoint of hydrolysis resistance, it is preferable to use a hydrolysis inhibitor (iii) having a high weight average molecular weight. The weight average molecular weight of the hydrolysis inhibitor (iii) is preferably 500 or more, more preferably 2000 or more, and even more preferably 3000 or more. The upper limit of the weight average molecular weight is usually 50,000.

[0106] If the molecular weight of the hydrolysis inhibitor (iii) is too small, the hydrolysis resistance tends to decrease, whereas if the molecular weight is too large, the compatibility with the polyester resins (i) and (ii) tends to decrease.

[0107] Among the hydrolysis inhibitors (iii), it is preferable to use a carbodiimide group-containing compound, and in this case, the carbodiimide equivalent is preferably 50 to 10,000, particularly 100 to 1,000, and further preferably 150 to 500. The carbodiimide equivalent indicates the chemical formula weight per one carbodiimide group.

[0108] The content of the hydrolysis inhibitor (iii) is preferably 0.01 to 10 parts by weight, particularly preferably 0.1 to 5 parts by weight, and further preferably 0.2 to 3 parts by weight, based on 100 parts by weight of the polyester resin (i) or (ii). If the content is too high, turbidity tends to occur due to poor compatibility with the polyester resin (i) or (ii), and if the content is too low, sufficient durability tends to be difficult to obtain.

[0109] The content of the hydrolysis inhibitor (iii) is preferably optimized depending on the acid value of the polyester resin (i) or (ii), and the molar ratio [(y) / (x)] of the total number of moles (y) of functional groups of the hydrolysis inhibitor (iii) in the pressure-sensitive adhesive composition to the total number of moles (x) of acidic functional groups of the polyester resin (i) or (ii) in the pressure-sensitive adhesive composition is preferably 0.5≦(y) / (x), particularly preferably 1≦(y) / (x)≦1000, and further preferably 1.5≦(y) / (x)≦100. If the molar ratio of (y) to (x) is too low, the moisture and heat resistance tends to decrease. If the molar ratio of (y) to (x) is too high, the compatibility with the polyester resin (i) or (ii) tends to decrease, and the adhesive strength, cohesive strength, and durability tend to decrease.

[0110] <Crosslinking agent (iv)> It is preferable that the pressure-sensitive adhesive composition of the present invention further contains a crosslinking agent (iv). By containing the crosslinking agent (iv), the polyester resin (i) or (ii) is crosslinked with the crosslinking agent (iv) to have excellent cohesive strength, thereby improving the performance as a pressure-sensitive adhesive.

[0111] Examples of such crosslinking agents (iv) include compounds having functional groups that react with at least one of the hydroxyl group and the carboxyl group contained in the polyester resins (i) and (ii), such as polyisocyanate compounds and polyepoxy compounds. In addition, polyfunctional acrylic monomers and urethane acrylate oligomers that increase the cohesive force even if they do not react with the polyester resins (i) and (ii) can also be used. Among these, it is particularly preferable to use polyisocyanate compounds, since they can achieve a good balance between initial adhesion, mechanical strength, and heat resistance.

[0112] Examples of such polyisocyanate compounds include polyisocyanates such as tetramethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, tolylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, tetramethylxylylene diisocyanate, 1,5-naphthalene diisocyanate, and triphenylmethane triisocyanate. In addition, examples of such polyisocyanate compounds include adducts of the above polyisocyanates with polyol compounds such as trimethylolpropane, and biuret and isocyanurate compounds of these polyisocyanate compounds. The above polyisocyanate compounds may also be used in which the isocyanate portion is blocked with phenol, lactam, or the like. These crosslinking agents (iv) may be used alone or in combination of two or more.

[0113] The content of the crosslinking agent (iv) can be appropriately selected depending on the molecular weight and intended use of the polyester resins (i) and (ii), but it is usually preferable that the crosslinking agent (iv) is contained in a ratio of 0.2 to 10 equivalents of reactive groups contained in the crosslinking agent (iv) per equivalent of at least one of the hydroxyl group and the carboxyl group contained in the polyester resin (i) or (ii), particularly preferably 0.5 to 5 equivalents, and further preferably 0.5 to 3 equivalents. If the equivalent number of reactive groups contained in the crosslinking agent (iv) is too small, the cohesive strength tends to decrease, and if it is too large, the flexibility tends to decrease.

[0114] The content of the crosslinking agent (iv) is preferably 0.01 to 10 parts by weight, particularly preferably 0.1 to 8 parts by weight, further preferably 0.5 to 6 parts by weight, and especially preferably 1 to 4 parts by weight, per 100 parts by weight of the polyester resin (i) or (ii). If the amount of such crosslinking agent is too small, the cohesive strength tends to decrease, whereas if the amount is too large, the flexibility tends to decrease and the required adhesive strength tends to be difficult to obtain.

[0115] In the reaction between the polyester resins (i) and (ii) and the crosslinking agent (iv), organic solvents that do not have functional groups that react with the components (i), (ii), and (iv) can be used, such as esters such as ethyl acetate and butyl acetate, ketones such as methyl ethyl ketone and methyl isobutyl ketone, and aromatics such as toluene and xylene. These can be used alone or in combination of two or more kinds.

[0116] <Urethanization catalyst (v)> In terms of reaction rate, the pressure-sensitive adhesive composition of the present invention preferably contains a urethanization catalyst (v).

[0117] Examples of the urethanization catalyst (v) include organometallic compounds, tertiary amine compounds, etc. These can be used alone or in combination of two or more kinds.

[0118] Examples of the organometallic compound include zirconium-based compounds, iron-based compounds, tin-based compounds, titanium-based compounds, lead-based compounds, cobalt-based compounds, and zinc-based compounds. Examples of the zirconium compound include zirconium naphthenate and zirconium acetylacetonate. Examples of iron-based compounds include iron acetylacetonate and iron 2-ethylhexanoate. Examples of the tin compounds include dibutyltin dichloride, dibutyltin oxide, and dibutyltin dilaurate.

[0119] Examples of titanium compounds include dibutyltitanium dichloride, tetrabutyltitanium, and butoxytitanium trichloride. Examples of lead-based compounds include lead oleate, lead 2-ethylhexanoate, lead benzoate, and lead naphthenate. Examples of the cobalt-based compounds include cobalt 2-ethylhexanoate and cobalt benzoate. Examples of zinc-based compounds include zinc naphthenate and zinc 2-ethylhexanoate. Examples of the tertiary amine compound include triethylamine, triethylenediamine, and 1,8-diazabicyclo-(5,4,0)-undecene-7.

[0120] Among these urethane catalysts (v), in terms of reaction speed and pot life of the adhesive layer, organometallic compounds are preferred, and zirconium compounds are particularly preferred. Furthermore, the urethane catalyst (v) is preferably used in combination with acetylacetone as a catalytic action inhibitor. The inclusion of acetylacetone is preferred in terms of inhibiting catalytic action at low temperatures and extending pot life.

[0121] The content of the urethane catalyst (v) is preferably 0.0001 to 1 part by weight, more preferably 0.001 to 0.1 part by weight, and even more preferably 0.01 to 0.05 part by weight, per 100 parts by weight of the polyester resin (i) or (ii). If the content is too low, the aging time until the crosslinking reaction is completed tends to be long, and if the content is too high, the adhesive properties tend to decrease.

[0122] <Antioxidants (vi)> The pressure-sensitive adhesive composition of the present invention preferably contains an antioxidant (vi) from the viewpoint of increasing the stability of the resin.

[0123] Examples of the antioxidant (vi) include hindered phenol-based antioxidants, amine-based antioxidants, sulfur-based antioxidants, phosphoric acid-based antioxidants, etc. Among them, at least one selected from the group consisting of hindered phenol-based antioxidants, amine-based antioxidants, and phosphoric acid-based antioxidants is preferred, and an antioxidant consisting of a hindered phenol-based compound is particularly preferred. Examples of the hindered phenol-based antioxidants include antioxidants having a hindered phenol structure in which a group with large steric hindrance, such as a tertiary butyl group, is bonded to at least one of the carbon atoms adjacent to the carbon atom on the aromatic ring to which the phenolic hydroxyl group is bonded.

[0124] The content of the antioxidant (vi) is preferably 0.01 to 10 parts by weight, more preferably 0.03 to 8 parts by weight, and further preferably 0.05 to 5 parts by weight, based on 100 parts by weight of the polyester resin (i) or (ii). If the content is too low, adhesive residue on the adherend tends to be more likely to occur, whereas if the content is too high, the adhesive properties tend to decrease.

[0125] <Tackifying resin (vii)> In the present invention, it is preferable to contain a tackifier resin (vii) in that the adhesive properties can be improved.

[0126] The tackifier resin (vii) is not particularly limited, and conventionally known resins can be used. Examples of the tackifier resin (vii) include hydrocarbon-based tackifier resins, terpene-based resins, phenol-based resins, rosin-based resins, xylene resins, epoxy-based resins, polyamide-based resins, ketone-based resins, and elastomer-based resins. These may be used alone or in combination of two or more. Among them, from the viewpoint of improving the adhesive properties, hydrocarbon-based tackifier resins, terpene-based resins, and rosin-based resins are preferred. In addition, it is particularly preferred that the tackifier resin (vii) contains at least one of a hydrocarbon-based tackifier resin and a terpene-based resin in terms of the stability of the adhesive, and further, a terpene-based resin is particularly preferred in terms of maintaining a high degree of bioplasticity and being compatible with physical properties. The content is preferably 30% by weight or more of the total tackifier resin, preferably 50% by weight or more, and preferably 70% by weight or more.

[0127] Examples of the hydrocarbon tackifier resin include various hydrocarbon resins such as aliphatic hydrocarbon resins, aromatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aliphatic / aromatic petroleum resins (styrene-olefin copolymers, etc.), aliphatic / alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone resins, coumarone-indene resins, etc. Commercially available products include, for example, "FTR6100", "FTR6110", "FTR6125", etc. manufactured by Mitsui Chemicals, Inc.

[0128] Examples of the terpene resin include terpene resin, terpene phenol resin, and aromatic modified terpene resin. Specifically, α-pinene polymer, β-pinene polymer, dipentene polymer, and terpene resin obtained by modifying them with phenol, aromatic, hydrogenation, or hydrocarbon can be used. Among them, terpene resin is preferred because it tends to have high adhesive strength after 24 hours of application, and terpene phenol resin is preferred because it has high adhesive strength to olefin. In addition, examples of commercially available products include "YS Polystar S145", "YS Resin PX1000", "YS Resin PX1250", "YS Polystar T145", "YS Resin TO115", "YS Polystar U130", and "Clearon P125" manufactured by Yasuhara Chemical Co., Ltd.

[0129] Examples of the phenolic resin that can be used include condensates of various phenols such as phenol, m-cresol, 3,5-xylenol, p-alkylphenol, and resorcin with formaldehyde. In addition, resol obtained by subjecting the phenols to an addition reaction with formaldehyde under an alkali catalyst, novolak obtained by subjecting the phenols to a condensation reaction with formaldehyde under an acid catalyst, and rosin-modified phenolic resin obtained by adding phenol to rosins such as unmodified or modified rosin or derivatives thereof under an acid catalyst and thermally polymerizing the phenol.

[0130] Examples of the rosin resin include rosin resin, polymerized rosin resin, hydrogenated rosin resin, rosin ester resin, hydrogenated rosin ester resin, rosin phenol resin, polymerized rosin ester, etc. Specifically, unmodified rosin (raw rosin) such as gum rosin, wood rosin, tall oil rosin, etc., modified rosins obtained by hydrogenating, disproportionating, polymerizing, or otherwise chemically modifying these, and derivatives of these can be used. In addition, examples of commercially available products include "Hariestar TF", "Haritac 8LJA", "Haritac PH", "Haritac FK100", "Haritac PCJ", etc. manufactured by Harima Chemicals Co., Ltd.

[0131] The tackifier resin (vii) preferably has an acid value of 30 mgKOH / g or less, particularly preferably 10 mgKOH / g or less, further preferably 3 mgKOH / g or less, and particularly preferably 1 mgKOH / g or less. When multiple types of tackifier resins are used in combination, the average of the above range is preferably used.

[0132] The softening point of the tackifier resin (vii) (measured, for example, by the ring and ball method) is preferably 80 to 170° C., particularly 85 to 160° C., and more preferably 95 to 150° C. If the softening point is within the above range, the adhesive properties (adhesive strength, cohesive strength) can be improved, which is preferable.

[0133] In the present invention, the tackifier resin (vii) is preferably a plant-derived resin in order to maintain a high bioplasticity of the entire adhesive. Examples of plant-derived tackifier resins include terpene resins and rosin resins.

[0134] The content of the tackifier resin (vii) is preferably 2 to 100 parts by weight, more preferably 5 to 80 parts by weight, even more preferably 6 to 50 parts by weight, particularly preferably 8 to 30 parts by weight, and especially preferably 9 to 20 parts by weight, relative to 100 parts by weight of the polyester resin (i) or (ii). If the content is too high, the pressure-sensitive adhesive layer tends to become too hard and the adhesion tends to decrease, whereas if the content is too low, the effect of the addition tends to be difficult to obtain.

[0135] In the pressure-sensitive adhesive composition of the present invention, in addition to the above-mentioned polyester resin (i) or (ii), hydrolysis inhibitor (iii), crosslinking agent (iv), urethanization catalyst (v), antioxidant (vi), and tackifier resin (vii), additives such as softeners, ultraviolet absorbers, stabilizers, and antistatic agents, as well as other additives such as inorganic or organic fillers, powders, and particulates such as pigments, may be blended within a range that does not impair the effects of the present invention. In addition, the pressure-sensitive adhesive composition may contain small amounts of impurities contained in the manufacturing raw materials of the pressure-sensitive adhesive components. These can be used alone or in combination of two or more.

[0136] The pressure-sensitive adhesive of the present invention is obtained by crosslinking the pressure-sensitive adhesive composition. Furthermore, the pressure-sensitive adhesive of the present invention preferably has a bioplasticity of 60% or more, more preferably 65% ​​or more, even more preferably 70% or more, and particularly preferably 80% or more. The bioplasticity of the pressure-sensitive adhesive can be adjusted by adjusting the types and amounts of the polyester resins (i) and (ii) and other blending components. The bioplastic degree of the PSA can be calculated as a weighted average of the bioplastic degree of the polyester resin determined by the above-mentioned method and the proportion of bio-derived carbon in each of the other components.

[0137] The bioplasticity of the pressure-sensitive adhesive can also be measured by the above-mentioned NMR method or a method based on ASTM D-6866 [measurement of natural radioactive carbon (C-14) concentration].

[0138] The pressure-sensitive adhesive of the present invention is an adhesive in which the pressure-sensitive adhesive composition is crosslinked, and the adhesive strength (α) under the following conditions is 1 N / 25 mm or more, more preferably 5 to 100 N / 25 mm, even more preferably 7 to 50 N / 25 mm, and particularly preferably 9 to 30 N / 25 mm. If the adhesive strength is too small, the adhesion reliability decreases. Adhesive strength (α): When an adhesive sheet is formed on a substrate with an adhesive layer made of an adhesive, it is attached to a SUS-BA plate adherend and left to stand for 30 minutes in an environment of 23°C and 50% RH, after which the 180-degree peel strength (N / 25 mm) at a peel speed of 300 mm / min against the adherend.

[0139] The pressure-sensitive adhesive sheet of the present invention has a pressure-sensitive adhesive layer containing the above-mentioned pressure-sensitive adhesive, and such a pressure-sensitive adhesive layer is preferably formed on one or both sides of a supporting substrate. In the present invention, the term "sheet" is used to include the meanings of "film" and "tape."

[0140] <Adhesive sheet> The pressure-sensitive adhesive sheet can be produced, for example, as follows. Such a pressure-sensitive adhesive sheet can be produced according to a known general pressure-sensitive adhesive sheet producing method. For example, the pressure-sensitive adhesive composition is applied to a substrate, dried, and a release sheet is attached to the opposite surface of the pressure-sensitive adhesive composition layer, followed by curing as necessary to obtain the pressure-sensitive adhesive sheet of the present invention having a pressure-sensitive adhesive layer containing a pressure-sensitive adhesive on a substrate.

[0141] Alternatively, the pressure-sensitive adhesive sheet of the present invention can be obtained by coating the pressure-sensitive adhesive composition on a release sheet, drying the composition, laminating a substrate to the opposite surface of the pressure-sensitive adhesive composition layer, and curing the resulting layer as necessary.

[0142] Alternatively, a substrate-less double-sided pressure-sensitive adhesive sheet can be produced by forming a pressure-sensitive adhesive layer on a release sheet and laminating a release sheet to the opposite side of the pressure-sensitive adhesive layer.

[0143] When using the resulting pressure-sensitive adhesive sheet or substrate-less double-sided pressure-sensitive adhesive sheet, the release sheet is peeled off from the pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer is attached to an adherend.

[0144] Examples of the substrate include polyester resins such as polyethylene naphthalate, polyethylene terephthalate, polybutylene terephthalate, and polyethylene terephthalate / isophthalate copolymer; polyolefin resins such as polyethylene, polypropylene, and polymethylpentene; polyethylene fluoride resins such as polyvinyl fluoride, polyvinylidene fluoride, and polyethylene fluoride; polyamides such as nylon 6 and nylon 6,6; vinyl polymers such as polyvinyl chloride, polyvinyl chloride / vinyl acetate copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, and vinylon; cellulose resins such as cellulose triacetate and cellophane; acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, polyethyl acrylate, and polybutyl acrylate; polystyrene; polycarbonate; polyarylate; polyimide; and sheets made of at least one synthetic resin selected from the group consisting of cycloolefin polymers; metal foils of aluminum, copper, and iron; paper such as fine paper and glassine paper; and woven and nonwoven fabrics made of glass fiber, natural fibers, synthetic fibers, and the like. These substrates can be used as a single layer or as a multi-layer structure in which two or more types are laminated.

[0145] Among these, substrates made of polyethylene terephthalate and polyimide are particularly preferred, with polyethylene terephthalate being particularly preferred in terms of excellent adhesion to pressure-sensitive adhesives.

[0146] The substrate may be a foam substrate, for example, a foam sheet made of a synthetic resin foam such as polyurethane foam, polyethylene foam, polyacrylate foam, etc. Among these, polyethylene foam and polyacrylate foam are preferred because of their excellent balance between conformability to the adherend and adhesive strength.

[0147] The thickness of the substrate is, for example, preferably from 1 to 1000 μm, particularly preferably from 2 to 500 μm, and further preferably from 3 to 300 μm.

[0148] As the release sheet, for example, a sheet made of any of the various synthetic resins exemplified above as the base material, paper, cloth, nonwoven fabric, etc. that has been subjected to a release treatment can be used. As the release sheet, it is preferable to use a silicone-based release sheet.

[0149] The pressure-sensitive adhesive composition may be applied using, for example, a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, a spray coater, a comma coater, or the like.

[0150] The conditions for the above-mentioned aging treatment are generally room temperature (23°C) to 70°C, and generally 1 to 30 days. Specifically, the treatment may be performed under conditions such as 23°C for 1 to 20 days, preferably 23°C for 3 to 14 days, or 40°C for 1 to 10 days.

[0151] As for drying conditions, the drying temperature is preferably 60 to 140° C., particularly preferably 80 to 120° C., and the drying time is preferably 0.5 to 30 minutes, particularly preferably 1 to 5 minutes.

[0152] The thickness of the adhesive layer of the above-mentioned adhesive sheet and substrate-less double-sided adhesive sheet is preferably 2 to 500 μm, particularly preferably 5 to 200 μm, and further preferably 10 to 100 μm. If the thickness of the adhesive layer is too thin, the adhesive strength tends to decrease, while if it is too thick, it becomes difficult to apply uniformly and problems such as air bubbles in the coating film tend to occur. In addition, when considering impact absorption, it is preferable to make the thickness 50 μm or more.

[0153] The thickness of the adhesive layer is determined by subtracting the measured thickness of the components other than the adhesive layer from the measured thickness of the entire adhesive sheet using a Mitutoyo ID-C112B.

[0154] The gel fraction of the adhesive layer of the adhesive sheet is preferably 10% by weight or more from the viewpoint of durability and adhesive strength, particularly preferably 20 to 80% by weight, further preferably 25 to 70% by weight, and particularly preferably 27 to 45% by weight. If the gel fraction is too low, the cohesive strength tends to decrease, resulting in a decrease in holding power. If the gel fraction is too high, the cohesive strength tends to increase, resulting in a decrease in adhesive strength.

[0155] The gel fraction is an indication of the degree of crosslinking, and is calculated, for example, by the following method. That is, an adhesive sheet (without a release sheet) in which an adhesive layer is formed on a polymer sheet (e.g., a PET film, etc.) serving as a substrate is wrapped in a 200-mesh SUS wire netting, and immersed in toluene at 23°C for 24 hours, and the weight percentage of the insoluble adhesive component remaining in the wire netting after immersion relative to the weight of the adhesive component before immersion is taken as the gel fraction. However, the weight of the substrate is subtracted.

[0156] Furthermore, such a pressure-sensitive adhesive sheet may be protected by providing a release sheet on the outer side of the pressure-sensitive adhesive layer, if necessary. In a pressure-sensitive adhesive sheet in which the pressure-sensitive adhesive layer is formed on one side of a substrate, the substrate may be subjected to a release treatment on the side opposite to the pressure-sensitive adhesive layer, and the release-treated surface may be used to protect the pressure-sensitive adhesive layer.

[0157] The pressure-sensitive adhesive of the present invention can be used for bonding various components, and in particular, it is used as a single-sided or double-sided pressure-sensitive adhesive sheet used for bonding optical components, for fixing components of portable electronic devices, and for fixing electronic components. EXAMPLES

[0158] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are by weight.

[0159] In the following examples, the bioplastic degree, ester group concentration, heat of crystalline fusion, weight average molecular weight, glass transition temperature, acid value, and gel fraction of the adhesive of the polyester resin were measured according to the methods described above.

[0160] A polyester resin was produced by the following method.

[0161] [Production Example 1: Production of polyester resin (i-1)] In a reaction vessel equipped with a thermometer, a stirrer, a distillation column, a nitrogen inlet tube and a vacuum device, 17.8 parts (0.45 moles) of sebacic acid as polyvalent carboxylic acids (a), 61.4 parts (0.55 moles) of hydrodistilled dimer acid (manufactured by Croda, "Pripol 1009"), 20.7 parts (1.7 moles) of ethylene glycol and 0.2 parts (0.0065 moles) of trimethylolpropane as polyol components (b), and 0.01 parts of tetrabutyl titanate as a catalyst were charged, and the internal temperature was gradually raised to 250 ° C., and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was raised to 260 ° C., and 0.01 parts of tetrabutyl titanate was charged as a catalyst, the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (i-1). The obtained polyester resin (i-1) had a bioplasticity of 92%, an ester group concentration of 4.64 mmol / g, a heat of crystalline fusion of 0 J / g, a weight-average molecular weight of 58,000, a glass transition temperature (Tg) of -50°C, and an acid value of 0.4 mg KOH / g. The plant-derived raw materials in Production Example 1 were sebacic acid and hydrodistilled dimer acid, and the content thereof relative to the polyester resin (i-1) was 86%.

[0162] [Production Example 2: Production of polyester resin (i-2)] In a reaction vessel equipped with a thermometer, a stirrer, a distillation column, a nitrogen inlet tube and a vacuum device, 84.3 parts (1.00 mol) of hydrodistilled dimer acid (manufactured by Croda, "Pripol 1009") as polyvalent carboxylic acids (a), 15.6 parts (1.7 mol) of ethylene glycol and 0.1 parts (0.0065 mol) of trimethylolpropane as polyol components (b), and 0.01 parts of tetrabutyl titanate as a catalyst were charged, and the internal temperature was gradually raised to 250 ° C., and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was raised to 260 ° C., 0.01 parts of tetrabutyl titanate was charged as a catalyst, the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (i-2). The obtained polyester resin (i-2) had a bioplasticity of 95%, an ester group concentration of 3.36 mmol / g, a crystalline fusion heat of 0 J / g, a weight-average molecular weight of 72,000, a glass transition temperature (Tg) of -47°C, and an acid value of 0.3 mg KOH / g. The plant-derived raw material in Production Example 2 was a hydrodistilled dimer acid, and its content in the polyester resin (i-2) was 90%.

[0163] [Production Example 3: Production of polyester resin (i-3)] In a reaction vessel equipped with a thermometer, a stirrer, a distillation column, a nitrogen inlet tube and a vacuum device, 80.6 parts (1.00 mol) of hydrodistilled dimer acid (manufactured by Croda, "Pripol 1009") as polyvalent carboxylic acids (a), 19.1 parts (1.5 mol) of 1.4-butanediol and 0.3 parts (0.015 mol) of trimethylolpropane as polyol components (b), and 0.01 parts of tetrabutyl titanate as a catalyst were charged, and the internal temperature was gradually raised to 250 ° C., and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was raised to 260 ° C., 0.01 parts of tetrabutyl titanate was charged as a catalyst, the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (i-3). The obtained polyester resin (i-3) had a bioplasticity of 86%, an ester group concentration of 3.21 mmol / g, a crystalline fusion heat of 0 J / g, a weight-average molecular weight of 71,000, a glass transition temperature (Tg) of -52°C, and an acid value of 0.3 mg KOH / g. The plant-derived raw material in Production Example 3 was a hydrodistilled dimer acid, and its content in the polyester resin (i-3) was 86%.

[0164] [Production Example 4: Production of polyester resin (i-4)] In a reaction vessel equipped with a thermometer, a stirrer, a distillation column, a nitrogen inlet tube and a vacuum device, 80.3 parts (1.00 mol) of hydrodistilled dimer acid (manufactured by Croda, "Pripol 1009") as polyvalent carboxylic acids (a), 7.9 parts (0.90 mol) of ethylene glycol, 11.7 parts (0.80 mol) of neopentyl glycol and 0.1 parts (0.0065 mol) of trimethylolpropane as polyol components (b), and 0.01 parts of tetrabutyl titanate as a catalyst were charged, and the internal temperature was gradually raised to 250 ° C., and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was raised to 260 ° C., 0.01 parts of tetrabutyl titanate was charged as a catalyst, the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (i-4). The resulting polyester resin (i-4) had a bioplasticity of 91%, an ester group concentration of 3.25 mmol / g, a heat of crystalline fusion of 0 J / g, a weight-average molecular weight of 72,000, a glass transition temperature (Tg) of -47°C, and an acid value of 0.2 mg KOH / g. The plant-derived raw material in Production Example 4 was hydrodistilled dimer acid, and its content in the polyester resin (i-4) was 87%.

[0165] [Production Example 5: Production of polyester resin (i-5)] In a reaction vessel equipped with a thermometer, a stirrer, a distillation column, a nitrogen inlet tube and a vacuum device, 17.0 parts (0.45 moles) of sebacic acid as polyvalent carboxylic acids (a), 58.5 parts (0.55 moles) of hydrodistilled dimer acid (manufactured by Croda, "Pripol 1009"), 24.3 parts (2.1 moles) of ethylene glycol and 0.2 parts (0.0065 moles) of trimethylolpropane as polyol components (b), and 0.01 parts of tetrabutyl titanate as a catalyst were charged, and the temperature was gradually raised to an internal temperature of 250°C, and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was raised to 260°C, 0.01 parts of tetrabutyl titanate was charged as a catalyst, the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (i-5). The obtained polyester resin (i-5) had a bioplasticity of 92%, an ester group concentration of 4.64 mmol / g, a crystalline fusion heat of 0 J / g, a weight-average molecular weight of 97,000, a glass transition temperature (Tg) of -50°C, and an acid value of 0.1 mg KOH / g. The plant-derived raw materials in Production Example 5 were sebacic acid and hydrodistilled dimer acid, and the content thereof relative to the polyester resin (i-5) was 86%.

[0166] [Production Example 6: Production of polyester resin (i-6)] In a reaction vessel equipped with a thermometer, a stirrer, a distillation column, a nitrogen inlet tube and a vacuum device, 84.3 parts (1.00 mol) of hydrodistilled dimer acid (manufactured by Croda, "Pripol 1009") as polyvalent carboxylic acids (a), 15.6 parts (1.7 mol) of ethylene glycol and 0.1 parts (0.0065 mol) of trimethylolpropane as polyol components (b), and 0.01 parts of tetrabutyl titanate as a catalyst were charged, and the internal temperature was gradually raised to 250 ° C., and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was raised to 260 ° C., 0.01 parts of tetrabutyl titanate was charged as a catalyst, the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (i-6). The resulting polyester resin (i-6) had a bioplasticity of 95%, an ester group concentration of 3.36 mmol / g, a heat of crystalline fusion of 0 J / g, a weight-average molecular weight of 88,000, a glass transition temperature (Tg) of -47°C, and an acid value of 0.1 mg KOH / g. The plant-derived raw material in Production Example 6 was a hydrodistilled dimer acid, and its content in the polyester resin (i-6) was 90%.

[0167] Comparative Production Example 1: Production of Polyester Resin (i'-1) In a reaction vessel equipped with a thermometer, a stirrer, a distillation column, a nitrogen inlet tube and a vacuum device, 49.2 parts (1.00 mol) of hydrodistilled dimer acid (manufactured by Croda, "Pripol 1009") as polyvalent carboxylic acids (a), 50.8 parts (1.09 mol) of dimer diol (manufactured by Croda, "Pripol 2033") as polyol component (b), and 0.01 parts of tetrabutyl titanate as a catalyst were charged, and the internal temperature was gradually increased to 200 ° C., and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was increased to 240 ° C., 0.01 parts of tetrabutyl titanate was charged as a catalyst, the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (i'-1). The obtained polyester resin (i'-1) had a bioplasticity of 100%, an ester group concentration of 1.78 mmol / g, a crystalline fusion heat of 0 J / g, a weight average molecular weight of 33,000, a glass transition temperature (Tg) of -50°C, and an acid value of 0.1 mg KOH / g. The plant-derived raw materials in Comparative Production Example 1 were hydrodistilled dimer acid and dimer diol, and the content thereof relative to the polyester resin (i'-1) was 100%.

[0168] Comparative Production Example 2: Production of Polyester Resin (i'-2) A reactor equipped with a heater, a thermometer, a stirrer, a rectification column, a nitrogen inlet tube, and a vacuum device was charged with 9.6 parts (0.2 mol) of isophthalic acid and 46.8 parts (0.8 mol) of sebacic acid as polyvalent carboxylic acids (a), 27.1 parts (0.900 mol) of neopentyl glycol, 13.0 parts (0.500 mol) of 1,4-butanediol, 3.0 parts (0.087 mol) of 1,6-hexanediol, and 0.5 parts (0.013 mol) of trimethylolpropane as polyol components (b), and 0.01 parts of tetrabutyl titanate as a catalyst, and the internal temperature was gradually raised to 250° C., and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was raised to 260° C., 0.01 part of tetrabutyl titanate was charged as a catalyst, the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (i'-2). The obtained polyester resin (i'-2) had a bioplasticity of 56%, an ester group concentration of 7.7 mmol / g, a crystalline fusion heat of 0 J / g, a weight-average molecular weight of 80,000, a glass transition temperature (Tg) of -49°C, and an acid value of 0.4 mg KOH / g. The plant-derived raw material in Comparative Production Example 2 was sebacic acid, and its content relative to the polyester resin (i'-2) was 52%.

[0169] Comparative Production Example 3: Production of Polyester Resin (i'-3) In a reaction vessel equipped with a thermometer, a stirrer, a distillation column, a nitrogen inlet tube and a vacuum device, 17.8 parts (0.45 moles) of sebacic acid as polyvalent carboxylic acids (a), 61.2 parts (0.55 moles) of hydrodistilled dimer acid (manufactured by Croda, "Pripol 1006"), 20.6 parts (1.387 moles) of 1,3-propanediol as polyol component (b), and 0.3 parts (0.013 moles) of trimethylolpropane, and 0.01 parts of tetrabutyl titanate as a catalyst were charged, and the internal temperature was gradually raised to 250 ° C., and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was raised to 260 ° C., and 0.01 parts of tetrabutyl titanate was charged as a catalyst, the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (i'-3). The obtained polyester resin (i'-3) had a bioplasticity of 100%, an ester group concentration of 4.49 mmol / g, a crystalline fusion heat of 0 J / g, a weight-average molecular weight of 112,000, a glass transition temperature (Tg) of -56°C, and an acid value of 0.5 mg KOH / g. The plant-derived raw materials of Comparative Production Example 3 were hydrodistilled dimer acid, sebacic acid, and 1,3-propanediol, and the contents of the hydrodistilled dimer acid and sebacic acid relative to the polyester resin (i'-3) were 83%.

[0170] Comparative Production Example 4: Production of Polyester Resin (i'-4) In a reaction vessel equipped with a thermometer, a stirrer, a distillation column, a nitrogen inlet tube and a vacuum device, 84.1 parts (1.00 mol) of hydrodistilled dimer acid (manufactured by Croda, "Pripol 1006") as polyvalent carboxylic acids (a), 15.6 parts (1.387 mol) of 1,3-propanediol as polyol component (b), and 0.3 parts (0.013 mol) of trimethylolpropane, and 0.01 parts of tetrabutyl titanate as a catalyst were charged, and the internal temperature was gradually raised to 250 ° C., and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was raised to 260 ° C., 0.01 parts of tetrabutyl titanate was charged as a catalyst, the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (i'-4). The obtained polyester resin (i'-4) had a bioplasticity of 100%, an ester group concentration of 3.28 mmol / g, a crystalline fusion heat of 0 J / g, a weight average molecular weight of 157,000, a glass transition temperature (Tg) of -52°C, and an acid value of 0.8 mg KOH / g. The plant-derived raw materials in Comparative Production Example 4 were hydrodistilled dimer acid and 1,3-propanediol, and the content of the hydrodistilled dimer acid relative to the polyester resin (i'-4) was 88%.

[0171] The compositions and physical properties of the polyester resins produced in the above Production Examples are shown in Tables 1 and 2 below.

[0172] [Table 1]

[0173] [Table 2]

[0174] The polyester resins produced in the above Production Examples were examined for bioplasticity, ester group concentration, and heat of crystalline fusion. As a result, (i-1) to (i-6) all satisfied the ranges specified in the present invention, and can be used as the polyester resin (i) or (ii) for the pressure-sensitive adhesive composition of the present invention.

[0175] On the other hand, the polyester resin (i'-2), which is a typical polyester resin for adhesives, has a bioplastic content of about 56%, which is insufficient in terms of reducing the burden on the environment.

[0176] Next, prior to preparing the pressure-sensitive adhesive composition, the following components were prepared. [Hydrolysis inhibitor (iii)] Carbodiimide compound (iii-1): "Carbodilite V-09GB" (manufactured by Nisshinbo Chemical Co., Ltd.) [Crosslinking agent (iv)] Isocyanate-based crosslinking agent (iv-1): "Coronate HX" (manufactured by Tosoh Corporation) Isocyanate-based crosslinking agent (iv-2): "Coronate L" (manufactured by Tosoh Corporation) [Urethanization catalyst (v)] Zirconium compounds (v-1): "Orgatics ZC-150" (manufactured by Matsumoto Fine Chemical Co., Ltd.) (diluted with acetylacetone to a solids concentration of 1%) [Antioxidants (vi)] Hindered phenol antioxidant (vi-1): "IRGANOX1010" (manufactured by BASF) [Tackifying resin (vii)] Aromatic hydrocarbon resin (vii-1): "FTR6100" (Mitsui Chemicals) (softening point: 95°C, acid value: less than 0.1 mgKOH / g) Bioplastic content: 0% Polymerized rosin ester (vii-2): "Haritac PCJ" (Harima Chemicals) (softening point: 118-128°C, acid value: 16mgKOH / g or less) Bioplastic content: 88% Special rosin ester (vii-3): "Super Ester A-100" (Arakawa Chemical Co., Ltd.) (softening point: 100°C, acid value: 10mgKOH / g or less) Bioplastic content: 99% Aromatic terpene (vii-4): "YS Resin TO115" (Yasuhara Chemical Co., Ltd.) (softening point: 115°C, acid value: 0mgKOH / g) Bioplastic content: 70% or more Terpene resin (vii-5): "YS Resin PX1000" (Yasuhara Chemical Co., Ltd.) (softening point: 110°C, acid value: 0mgKOH / g) Bioplastic content: 90% or more

[0177] Next, pressure-sensitive adhesive compositions were prepared using the polyester resins (i-1 to i-6 and i'-1 to i'-4) obtained above, and pressure-sensitive adhesive sheets were produced according to the following Examples and Comparative Examples.

[0178] [Example 1] The polyester resin (i-1) obtained above was diluted with ethyl acetate to a solid content concentration of 50%, and 1 part (solid content) of a carbodiimide compound (iii-1), 2 parts (solid content) of an isocyanate crosslinking agent (iv-2), 0.02 parts (solid content) of a zirconium compound (v-1), and 0.1 parts (solid content) of a hindered phenol antioxidant (vi-1) were blended with 100 parts of the solid content, and the mixture was stirred and mixed to obtain a pressure-sensitive adhesive composition. The obtained adhesive composition was applied to a polyethylene terephthalate (PET) film (thickness 38 μm) so that the thickness after drying would be about 25 μm, and then dried for 3 minutes at 100° C. to form an adhesive layer. Thereafter, a release-treated PET film (release film) was attached to the adhesive layer to protect its surface, and the layer was aged in an atmosphere at a temperature of 40° C. for 10 days to obtain an adhesive sheet.

[0179] [Examples 2 to 14, Comparative Examples 1 to 7] The same procedure as in Example 1 was carried out except that the ingredients were blended as shown in Table 3 below, to prepare a pressure-sensitive adhesive composition and obtain a pressure-sensitive adhesive sheet.

[0180] [Table 3]

[0181] The following evaluations were carried out on the obtained pressure-sensitive adhesive sheets of Examples 1 to 14 and Comparative Examples 1 to 7. The evaluation results are shown in Table 4 below.

[0182] <Adhesive strength (peel strength) (to SUS-BA)> A SUS-BA plate was prepared as an adherend. The adhesive sheet obtained above was cut to 25 mm x 200 mm in an environment of 23 ° C and 50% RH, and then the release film was peeled off, the adhesive layer side was abutted against a SUS-BA plate, and a 2 kg roller was reciprocated to pressurize and attach it. Then, after leaving it for 30 minutes in the same atmosphere, the 180 degree peel strength (N / 25 mm) was measured at a peel speed of 300 mm / min using an autograph (Shimadzu Corporation, Autograph AGS-H 500N) and evaluated according to the following criteria. (Evaluation Criteria) ◎...5N / 25mm or more. ○···More than 1N / 25mm, less than 5N / 25mm. ×...Less than 1N / 25mm.

[0183] <Adhesive strength after 24 hours (peel strength after 24 hours)> A SUS-BA plate was prepared as an adherend. The adhesive sheet obtained above was cut to 25 mm x 200 mm in an environment of 23 ° C and 50% RH, and then the release film was peeled off, the adhesive layer side was placed against the SUS-BA plate, and a 2 kg roller was pressed and applied back and forth. After leaving it for 24 hours in the same atmosphere, the 180 degree peel strength (N / 25 mm) was measured at a peel speed of 300 mm / min using an autograph (Shimadzu Corporation, Autograph AGS-H 500N) and evaluated according to the following criteria. (Evaluation Criteria) ◎...20N / 25mm or more. ○···13N / 25mm or more, less than 20N / 25mm. ×...Less than 13N / 25mm.

[0184] <Adhesive strength (peel strength) (against PP)> A polypropylene plate (PP) (manufactured by Nippon Testpanel Co., Ltd., PP 2.0×70×150 mm) was prepared as an adherend. The adhesive sheet obtained above was cut to 25 mm×200 mm in an environment of 23° C. and 50% RH, and then the release film was peeled off, the adhesive layer side was brought into contact with a polypropylene plate (PP) plate, and a 2 kg roller was reciprocated to pressurize and attach it. Then, after leaving it for 30 minutes in the same atmosphere, the 180° peel strength (N / 25 mm) was measured at a peel speed of 300 mm / min using an autograph (manufactured by Shimadzu Corporation, Autograph AGS-H 500N), and evaluated according to the following criteria. (Evaluation Criteria) ◎...10N / 25mm or more. ○ More than 6N / 25mm, less than 10N / 25mm. ×...Less than 6N / 25mm.

[0185] <Holding force (cohesive force)> The pressure-sensitive adhesive sheet obtained above was attached to a substrate of SUS304 in accordance with JIS Z-0237 with an area of ​​25 mm x 25 mm, and then left to stand at 80°C for 20 minutes. A load of 1 kg was then applied to the sheet, and the time until it fell was measured, or for sheets that did not fall after being left to stand for 24 hours, the displacement after 24 hours was measured, and the sheet was evaluated according to the following criteria. (Evaluation Criteria) ○ No falling even after being left undisturbed for 24 hours. ×: The sample fell off after being left to stand for 24 hours.

[0186] <Mark resistance> The above adhesive composition was applied to a polyethylene terephthalate (PET) film (thickness 38 μm) as a substrate so that the thickness after drying would be about 25 μm, and then dried for 3 minutes at 100° C. to form an adhesive layer. Thereafter, a release-treated PET film (release film) was attached to the above adhesive layer, and a 2 kg roller was placed on top of the release film, and after stopping for 10 seconds, the adhesive layer was visually observed and evaluated according to the following criteria. (Evaluation Criteria) ○ No change. × There are dents where the roller was placed.

[0187] <Workability> The adhesive sheet obtained above was cut into a width of 25 mm with a cutter knife, and adhesion of the adhesive to the blade of the cutter knife was visually observed and evaluated according to the following criteria. (Evaluation Criteria) ○The glue did not stick to the blade. × Glue got on the blade.

[0188] <Transparency> The release film was peeled off from the adhesive layer of the adhesive sheet obtained above, and the exposed adhesive layer was attached to an alkali-free glass plate (Eagle XG, manufactured by Corning Incorporated) to prepare a test specimen having a configuration of PET film / adhesive layer / alkali-free glass plate. The haze of this test piece was measured using a HAZE MATER NDH2000 (manufactured by Nippon Denshoku Industries Co., Ltd.), and the haze value of the PET film was subtracted to obtain the haze value of the adhesive sheet, which was then evaluated according to the following criteria. The haze meter complies with JIS K7361-1. ○ Haze is 3 or less. △ Haze is greater than 3 and less than 10. × Haze exceeds 10.

[0189] [Table 4]

[0190] From the results in Table 4, the pressure-sensitive adhesive sheets of Examples 1 to 14 had the desired adhesive properties not only for metal adherends, but also for adherends that are difficult to adhere to, such as polyolefin resins, and had an excellent balance between adhesive strength and holding power. Furthermore, the pressure-sensitive adhesive sheets of Examples 1 to 14 had excellent resistance to dents when produced, even when narrowed, and excellent processability as pressure-sensitive adhesive sheets, as well as excellent processability and transparency when laminated. Furthermore, it can be seen that the inclusion of a tackifier resin provides even better adhesive properties, and adhesive properties over time. In contrast, the adhesives of Comparative Examples 1 to 3, which used conventional polyester resins with a high degree of bioplasticity, did not have satisfactory adhesive properties, and the adhesive layer was too soft, causing dents, and was poor in processability and transparency. Furthermore, the adhesives of Comparative Examples 1 and 3 to 7, which used polyester resins that did not use glycols with an even number of carbon atoms as the polyol component, had insufficient adhesion to polyolefin resins, or were poor in balance between adhesion and holding power.

[0191] In the above embodiment, specific embodiments of the present invention are shown, but the above embodiment is merely illustrative and should not be interpreted as being limiting. Various modifications that are obvious to those skilled in the art are intended to be within the scope of the present invention. [Industrial Applicability]

[0192] The adhesive of the present invention uses environmentally friendly plant-derived raw materials, and even when a polyester-based resin with a high degree of bioplasticity is used, it has good adhesive properties on various substrates such as metals and plastics, and has excellent processability, dent resistance, and transparency even when made narrow, and is used as a single-sided or double-sided adhesive sheet used for bonding optical components, a single-sided or double-sided adhesive sheet for fixing components of portable electronic devices, and a single-sided or double-sided adhesive sheet for fixing electronic components.

Claims

1. A pressure-sensitive adhesive obtained by crosslinking a pressure-sensitive adhesive composition containing a polyester resin (i) having a structural portion derived from a polyvalent carboxylic acid (a) and a structural portion derived from a polyol component (b) and a crosslinking agent (iv), The polyester resin (i) contains 60% by weight or more of a structural portion derived from at least one selected from the group consisting of dimer acids, sebacic acids, and dimer diols, based on the weight of the polyester resin (i); As the polyol component (b), a glycol (b1) having an even number of carbon atoms (excluding dimer diol) ) The polyester resin (i) has an ester group concentration of 2 mmol / g or more and a crystalline heat of fusion measured by a differential scanning calorimeter of 10 J / g or less; the content of the crosslinking agent (iv) is 0.01 to 10 parts by weight based on 100 parts by weight of the polyester resin (i); An adhesive characterized in that the adhesive strength (α) under the following conditions is 1 N / 25 mm or more. Adhesive strength (α): When an adhesive sheet having an adhesive layer made of an adhesive formed on a substrate is formed, the sheet is attached to an adherend made of a SUS-BA plate and allowed to stand for 30 minutes in an environment of 23°C and 50% RH. The 180-degree peel strength (N / 25 mm) from the adherend is measured at a peel speed of 300 mm / min.

2. The adhesive according to claim 1, characterized in that the glycol (b1) having an even number of carbon atoms is an aliphatic glycol having a straight chain structure.

3. 3. The pressure-sensitive adhesive according to claim 1, wherein the polyvalent carboxylic acids (a) contain 70 mol % or less of linear carboxylic acids (a1).

4. The pressure-sensitive adhesive according to any one of claims 1 to 3, characterized in that the polyol component (b) contains 10 to 100 mol % of a glycol (b1) having an even number of carbon atoms.

5. The pressure-sensitive adhesive according to any one of claims 1 to 4, characterized in that the glycol (b1) having an even number of carbon atoms is a polyol having 4 or less carbon atoms.

6. The pressure-sensitive adhesive according to any one of claims 1 to 5, characterized in that the acid value of the polyester resin (i) is 10 mgKOH / g or less.

7. The pressure-sensitive adhesive according to any one of claims 1 to 6, characterized in that the polyester resin (i) has a bioplasticity of 60% or more.

8. A pressure-sensitive adhesive obtained by crosslinking a pressure-sensitive adhesive composition containing a polyester resin (ii) having a bioplastic content of 60% or more and a crosslinking agent (iv), the polyester resin (ii) has a structural portion derived from a polyvalent carboxylic acid (a) and a structural portion derived from a polyol component (b); The polyvalent carboxylic acids (a) include linear carboxylic acids having 4 to 12 carbon atoms, As the polyol component (b), a glycol (b1) having an even number of carbon atoms (excluding dimer diol) ) The polyester resin (ii) has an ester group concentration of 2 mmol / g or more and a crystalline heat of fusion measured by a differential scanning calorimeter of 10 J / g or less, the content of the crosslinking agent (iv) is 0.01 to 10 parts by weight based on 100 parts by weight of the polyester resin (ii); An adhesive characterized in that the adhesive strength (α) under the following conditions is 1 N / 25 mm or more. Adhesive strength (α): When an adhesive sheet having an adhesive layer made of an adhesive formed on a substrate is formed, the sheet is attached to an adherend made of a SUS-BA plate and allowed to stand for 30 minutes in an environment of 23°C and 50% RH. The 180-degree peel strength (N / 25 mm) from the adherend is measured at a peel speed of 300 mm / min.

9. The pressure-sensitive adhesive according to any one of claims 1 to 8, characterized in that the pressure-sensitive adhesive composition further contains a hydrolysis inhibitor (iii).

10. The pressure-sensitive adhesive according to any one of claims 1 to 9, characterized in that the pressure-sensitive adhesive composition further comprises a tackifier resin (vii).

11. The pressure-sensitive adhesive according to any one of claims 1 to 10, characterized in that the pressure-sensitive adhesive has a bioplasticity of 60% or more.

12. The pressure-sensitive adhesive according to any one of claims 1 to 11, which is used for bonding members.

13. A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer containing the pressure-sensitive adhesive according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Low moisture permeability pressure-sensitive adhesive sheet

    JP2007308626A

  • Polyester, polyester composition, adhesive composition, adhesive layer, and adhesive sheet

    JP2010037463A

  • Double-sided self-adhesive sheet

    JP2011088961A

  • Laminate

    JP2012036278A

  • Polymer derived from dehydroabietic acid and use thereof

    JP2012107175A